Factors affecting the adoption of new technologies by poplar growers in North Iran (Case study: Sowmeh Sara City) - Reza Roohi; Mohammad Hossien Menhaj; Mohammad Kavoosi-Kalashami (Caspian Journal of Environmental Sciences, 2021)
The purpose of this study is to determine the factors affecting the adoption of new technologies by poplar growers in Sowmeh Sara City, Guilan Province, north of Iran. The statistical population of the study includes poplar growers in the city. A total of 200 individuals were examined based on Cochran's formula and cluster sampling method at 2018. Structural equation modeling (SEM) was used to examine the impact of attitudes toward technology, understanding the use of technology, technological features, and social participation on the adoption of new technologies. Understanding the use of technology and social participation, and their constituent items, have had the greatest impact on the adoption of new technologies by poplar growers in Sowmeh Sara City. Accurate and transparent information about the features of new technologies and their differences with traditional methods is the key strategy in introducing these technologies and it will lead to adoption by poplar growers.